“Producción de semilla a escala piloto de hongos comestibles nativos en la provincia de San Martín” - Ríos Ruiz, Winston Franz (2015)
Cultivation of edible mushrooms is an activity that could contribute to the household economy. However, a limiting factor is having the mycelium ("seed") of the fungus to be produced. The objective óf this work was to obtain the "seed" of two native edible fungus (Auricu/aria spp. and Pleurotus spp.). Fruiting bodies of these fungi were collected from 3 areas of conservation of the Province of San Martin and transferred to the laboratory of Microbiology, Faculty of Agricultura! Sciences of the National University of San Martín, where were grown in petri dishes containing potato dextrose agar. The radial mycelial growth was statistically different in the different plates. Subsequently, pieces of 1 cm2 of culture medium were placed in bottles containing corn grains previously sterilized. The mycelium covered 100% of the grains of corn at 35 days for Auricularia spp. and 40 days for Pleurotus spp. To get an idea of mycelial growth in agroindustrial substrates, coffee pulp, rice husks and sawdust were used. At 40 days, the mycelium of Auricu/aria spp. covered 60% of coffee pulp substrate and 30% of rice husks. In the case of Pleurotus spp. covered 80% of coffee pulp substrate and 10% of rice husks. The results obtained show that the pulp of coffee and rice husks are promising for use as a substrate in the cultivation of edible fungus native remains.